1994
DOI: 10.1093/oxfordjournals.jbchem.a124357
|View full text |Cite
|
Sign up to set email alerts
|

Elastase Inhibitor Elafin Is a New Type of Proteinase Inhibitor Which Has a Transglutaminase-Mediated Anchoring Sequence Termed “Cementoin”1

Abstract: Elafin was shown to be a new type of proteinase inhibitor which has an anchoring sequence. Human elafin, a potent inhibitor specific for elastase and proteinase 3, has a unique repeating sequence in its prosegment that is rich in Gln and Lys residues. The prosegment, termed "cementoin," exhibits high homology with the repetitive element of seminal vesicle clotting protein, which is known as a good substrate for prostate transglutaminase. The cross-linking of cementoin by tissue transglutaminase showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
137
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(142 citation statements)
references
References 3 publications
4
137
0
1
Order By: Relevance
“…In the cornified cell envelope of the epidermis, both molecules are cross-linked to several proteins (including involucrin, keratin-1, loricrin, cystatin ␣, filaggrin) and are thought to function as cross-bridging molecules (47). In tracheal epithelium, trappin-2/elafin is also found in a complexed form (4). Previous in vitro studies showed that trappin-2 and/or elafin can covalently bind to a number of ECM proteins including elastin, fibronectin, laminin, fibrinogen, collagen, and ␤-crystallin by transglutamination (4,5,48).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the cornified cell envelope of the epidermis, both molecules are cross-linked to several proteins (including involucrin, keratin-1, loricrin, cystatin ␣, filaggrin) and are thought to function as cross-bridging molecules (47). In tracheal epithelium, trappin-2/elafin is also found in a complexed form (4). Previous in vitro studies showed that trappin-2 and/or elafin can covalently bind to a number of ECM proteins including elastin, fibronectin, laminin, fibrinogen, collagen, and ␤-crystallin by transglutamination (4,5,48).…”
Section: Discussionmentioning
confidence: 99%
“…In tracheal epithelium, trappin-2/elafin is also found in a complexed form (4). Previous in vitro studies showed that trappin-2 and/or elafin can covalently bind to a number of ECM proteins including elastin, fibronectin, laminin, fibrinogen, collagen, and ␤-crystallin by transglutamination (4,5,48). The transglutaminase-mediated cross-linking of trappin-2 and elafin to fibronectin and elastin was demonstrated to preserve their antiprotease activity and to protect the associated ECM molecule against proteolysis mediated by NE (5,48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now porcine SPAI-2 (2) and the proteinase inhibitor SKALP/elafin/elastase-specific inhibitor were described in the literature (1, 7, 17, 37). For the NH 2 -terminal TGase substrate domain a separate name, cementoin, was coined by Nara et al (20). Here we propose to give these proteins the acronym Trappin (Trappin ϭ TRansglutaminase substrate and WAP motif-containing ProteIN) as a new nomenclature for this protein family.…”
Section: Cloning and Sequence Analysis Of Bovine And Simian Skalp/elamentioning
confidence: 99%
“…The NH 2 -terminal domain, containing the TGase substrate motifs, is homologous to the guinea pig seminal vesicle protein-1 (19) and the human semenogelins (15). We showed that the NH 2 -terminal TGase substrate domain, for which the name "cementoin" was coined by others (20), is actually used in vivo and in vitro for cross-linking to stratum corneum proteins. Recently, it was shown by direct sequencing of cross-linked peptides from human foreskin epidermis that SKALP/elafin is cross-linked in vivo to loricrin and cytokeratin-1 (21), which are structural proteins of the terminally differentiating keratinocyte.…”
mentioning
confidence: 99%